Zakat Distribution Management: A Systematic Literature Review - Maisyarah, Anisa; Hamzah, Muhammad Zilal (Universitas Muhammadiyah Surakarta, 2024)
The social function of zakat as a maliyah ijtimaliyah worship will be optimized if there is minimal risk during the distribution process (disbursement risk). This can be achieved when stakeholders directly involved in the distribution process employ effective strategies and possess knowledge of zakat distribution management. This study delves into the literature discussing issues related to zakat distribution management over the past decade. Utilizing a qualitative approach with a systematic literature review, data were sourced from articles indexed by Scopus and Google Scholar. The data collection was facilitated using the Publish or Perish (PoP) software. Selected articles underwent analysis using the VOS Viewer tool to discern trends in the literature concerning zakat distribution management. The findings emphasize the importance of policymakers collaborating with specific entities to oversee zakat funds effectively. Furthermore, enhancing administrative and managerial competencies is crucial. Implementation of wakalah and mudharabah methods is recommended, along with leveraging technology's role in the contemporary digital landscape. The study underscores the significance of proactive measures to mitigate risks and optimize the social impact of zakat distribution. By fostering collaboration, enhancing competencies, and embracing innovative methods, stakeholders can ensure the efficient and equitable distribution of zakat funds. These efforts are essential for fulfilling the socio-religious obligations associated with zakat and maximizing its potential to alleviate poverty and promote social welfare.